SOSIALISASI MEMBANGUN KARAKTER UNGGUL PESERTA DIDIK MELALUI PENERAPAN PENDIDIKAN KARAKTER DI SEKOLAH - Muhammad Iqbal; Rambang Muharramsyah; Juwandi; Julita Dewi; Misraini; Mariah Kubtiah; Ruhamah; Zikriatun Ilmi (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service aimed to describe the various strategies carried out by schools in implementing character education through school culture at SMP Negeri 4 Takengon as a form of implementation of the Al-Muslim University collaboration. Character education is the lifeblood of education for the younger generation. To determine the achievement of increasing target participants' understanding and knowledge, instruments were used in the form of pretest and posttest questionnaires before and after the activity. Meanwhile, for feedback on the implementation of subsequent community service activities, participants were asked to respond regarding satisfaction or dissatisfaction with the management of the activity through a satisfaction questionnaire which was distributed directly after the end of the activity. From the implementation of community service  activity,  it was concluded that: 1) the character of students is formed in accordance with applicable values ​​and norms; 2) the formation of superior student character, respecting the process as students, loving others, appreciating and respecting teachers; 3) can identify and map students' character problems so that the solutions offered are in accordance with the characteristics of the problems faced. Especially for teenagers, the teacher is a model that will be imitated by students, so a learning method that combines knowledge, reflection and practice is needed. Thus, a new teacher orientation is needed in educating character, namely the ability to empower and develop society.